Frontal Brain Activity and Behavioral Indicators of Affective States are Weakly Affected by Thermal Stimuli in Sheep Living in Different Housing Conditions - Vögeli, Sabine; Wolf, Martin; Wechsler, Beat; Gygax, Lorenz (Frontiers in Veterinary Science, 2015)
Many stimuli evoke short-term emotional reactions. These reactions may play an important role in assessing how a subject perceives a stimulus. Additionally, long-term mood may modulate the emotional reactions but it is still unclear in what way. The question seems to be important in terms of animal welfare, as a negative mood may taint emotional reactions. In the present study with sheep, we investigated the effects of thermal stimuli on emotional reactions and the potential modulating effect of mood induced by manipulations of the housing conditions. We assume that unpredictable, stimulus-poor conditions lead to a negative and predictable, stimulus-rich conditions to a positive mood state. The thermal stimuli were applied to the upper breast during warm ambient temperatures: hot (as presumably negative), intermediate, and cold (as presumably positive). We recorded cortical activity by functional near-infrared spectroscopy, restlessness behavior (e.g. locomotor activity, aversive behaviors) and ear postures as indicators of emotional reactions. The strongest hemodynamic reaction was found during a stimulus of intermediate valence independent of the animal’s housing conditions, whereas locomotor activity, ear movements and aversive behaviors were seen most in sheep from the unpredictable, stimulus-poor housing conditions, independent of stimulus valence. We conclude that, sheep perceived the thermal stimuli and differentiated between some of them. An adequate interpretation of the neuronal activity pattern remains difficult, though. The effects of housing conditions were small indicating that the induction of mood was only modestly efficacious. Therefore, a modulating effect of mood on the emotional reaction was not found.